Pediatric Acute Alcohol Intoxication Admitted to the ICU: A Review of 102 Cases in France. Issue 9 (September 2021) - Ruetsch, Valerie; Zarka, Jonathan; Vanel, Blandine; Tissieres, Pierre; Megarbane, Bruno; Renolleau, Sylvain; Dauger, Stéphane; Guilbert, Anne-Sophie; Leteurtre, Sylvain; Charpentier, Julien; Vaugier, Isabelle; Bergounioux, Jean
Abstract : OBJECTIVES: To describe the profile and clinical outcomes of children (<18 yr) admitted to intensive care for acute alcohol intoxication, with special attention to complications and to the subgroup that required intubation. DESIGN: Retrospective observational study. SETTING: Seven pediatric and three adult ICUs in France. PATIENTS: Children 1–17 yr admitted to intensive care for acute alcohol intoxication between January 1, 2010, and December 30, 2017. INTERVENTIONS: The study was observational and patients received standard care. MEASUREMENTS AND MAIN RESULTS: We included 102 patients, with 71 males (69.6%) and 31 females (30.4%). Mean age was not different between males and females (14.0 ± 3.0 yr [range, 2–17 yr] and 14.2 ± 1.3 yr [range, 11–17 yr]; p = 0.67); six children were younger than 10 years. Mean blood alcohol concentration was not significantly different in males and females (2.42 ± 0.86 and 2.20 ± 0.54 g/L, respectively; p = 0.51). Of the 102 patients, 58 (57%) required intubation. Factors significantly associated with requiring intubation were lower Glasgow Coma Scale score ( p = 0.002), lower body temperature ( p = 0.045), and higher blood alcohol concentration ( p = 0.012); vascular filling, and electrolyte disturbances were not associated with needing intubation. Mean intubation time was 9.7 ± 5.2 hours. Among the 59 patients with Glasgow Coma Scale score less than 8, 12 did not require intubation. The most common metabolic disturbance was a high lactate level (48%), followed by hypokalemia (27.4%); 59 (58.2%) patients had hyperglycemia and three had hypoglycemia. CONCLUSIONS: Male adolescents make up the majority of pediatric patients admitted to intensive care for acute alcohol intoxication. A need for intubation was associated with a worse Glasgow Coma Scale, lower body temperature, and higher blood alcohol concentration. Intubation was usually required for less than 12 hours. Other acute medical complications reported in adults with acute alcohol intoxication, such as electrolyte disturbances and aspiration pneumonia, were rare in our pediatric patients. Abstract : Supplemental Digital Content is available in the text.